THE VALUE OF LAW IN THE WORKS OF S. S. ALEKSEEV AND MODERN ASSESSMENTS OF LAW (EUROPEAN AND ASIAN LAW REVIEW, 2024)
This article analyzes the scientific works of Professor S. S. Alekseev devoted to the social value of law in society. The article is preceded by the author’s personal memoirs, during his full-time postgraduate studies, about S. S. Alekseev. The author traces the development of the scientist’s ideas in legal science in the Soviet and post-Soviet periods.
Keywords: axiology; value; assessments; social value of law; instrumental value of law; theory of values